Effectiveness of Career Information Services in Career Planning for Junior High School Students - Sari, Donata; Astuti, Indri; Putri, Amallia (International Journal of Learning and Instruction (IJLI), 2023)
This study aimed to find out how well career information services help students plan their careers. The pre-experimental design method, with one group of pre-and post-test designs, was used in this study. The participants in this study were 261 students in eight grade at SMPN 2 Sungai Raya. They were inspecting utilizing likelihood testing with a straightforward irregular examining strategy. Therefore, 40 students were used as samples in this study. The study's results before students received career information services showed that only 60.80% of students planned their careers, whereas the results after students received career information showed an increase of 78.59%. Based on the results of the Effect Size t-test with Cohen'd at 2.35, it can be concluded that this study improves student career planning. It indicates that career information services play a very large role in enhancing student career planning.  Keywords: Career Information Services, Career Planning, Junior High School Students